Building black box circuit simulators to test and improve pupils' problem-solving ability. (3rd August 2018) - Harrison, Mark
Abstract: Putting an electrical circuit within an inaccessible black box and asking pupils to deduce what wiring is contained within the box based solely on the circuit's behaviour is a simple teaching idea with a long history. Problems arise when trying to build enough physical black boxes to simulate a larger number of circuits within a typical school's storage limitations. A solution is described which uses a microcontroller to simulate a large number of separate circuits within a single black box.